Borderland on the Isthmus : Race, Culture, and the Struggle for the Canal Zone - Donoghue, Michael E. (Book collections on Project MUSE., 2014)
The construction, maintenance, and defense of the Panama Canal brought Panamanians, U.S. soldiers and civilians, West Indians, Asians, and Latin Americans into close, even intimate, contact. In this lively and provocative social history, Michael E. Donoghue positions the Panama Canal Zone as an imperial borderland where U.S. power, culture, and ideology were projected and contested. Highlighting race as both an overt and underlying force that shaped life in and beyond the Zone, Donoghue details how local traditions and colonial policies interacted and frequently clashed. Panamanians respo.